Air power against terror : America's conduct of Operation Enduring Freedom - Lambeth, Benjamin S. (RAND Corp., 2005)
The terrorist attacks of 9/11 plunged the United States into a determined counteroffensive against Osama bin Laden and his al Qaeda terrorist network. This report details the initial U.S. military response to those attacks, namely, the destruction of al Qaeda's terrorist infrastructure and the removal of the ruling Taliban regime in Afghanistan. It first outlines the efforts of the Bush administration to prepare for war, including pulling together an effective coalition, crafting a war strategy, moving forces and materiel to the region, forging alliances with indigenous anti-Taliban elements in Afghanistan, laying the groundwork for a target-approval process, and planning for humanitarian relief operations. It then follows the unfolding of Operation Enduring Freedom from its beginning, starting with air strikes against Taliban early warning radars, airfields, ground force facilities, and other fixed targets. The author also explains how allied Special Operations Forces (SOF) were successfully inserted into Afghanistan and how those forces, enabled by U.S. air power, were eventually able to work with indigenous friendly Afghan fighters in defeating and routing the Taliban. He then outlines problems that were later encountered in Operation Anaconda- an initiative by U.S. Army forces to push into the high mountains of Afghanistan where hard-core al Qaeda holdouts were known to be regrouping. This was to be a conventional ground force operation, but unexpected resistance and resultant fierce fighting required the emergency summoning of fixed-wing air power. This air involvement proved pivotal in producing a successful outcome and, in hindsight, pointed to the failure of Operation Anaconda's planners to make the most of the potential synergy of air, space, and land power that was available to them. The author describes some of the friction and conflicts that arose within U.S. Central Command (CENTCOM) over how best to use air power in the war. Perhaps the most serious inefficiency had to do with strict rules of engagement and a resultant target-approval bottleneck at CENTCOM that often allowed many important but fleeting attack opportunities to slip away. The author emphasizes, however, several distinctive achievements in this war, including the use of SOF-enabled precision weapons that were effective irrespective of weather, the first combat use of Predator unmanned aerial vehicles armed with Hellfire missiles, and the integrated employment of high-altitude drones and other air- and space-based sensors that gave CENTCOM unprecedented round-the-clock awareness of enemy activity.